Non-canonical Expression of Cardiac Troponin-T in Neuroendocrine Ethmoid Sinus Carcinoma Following Immune Checkpoint Blockade - Tsuruda, Toshihiro; Sato, Yuichiro; Kajihara, Kei; Kawabata, Takayuki; Kubuki, Yoko; Komaki, Soichi; Kikuchi, Masao; Ishikawa, Tetsunori; Tono, Tetsuya; Kitamura, Kazuo (Frontiers in Cardiovascular Medicine, 2019)
We describe the case of a patient with neuroendocrine ethmoid sinus carcinoma, who exhibited markedly elevated levels of serum cardiac troponin-T and creatine kinase (CK)-MB isoenzyme without any symptom after the administration of nivolumab, immune checkpoint inhibitor. The repeated 12-leads-electrocardiogram did not show any changes in the ST-T segments or arrhythmias. The echocardiogram showed normal ranges of left ventricular contraction in the clinical course. Cardiac magnetic resonance imaging showed minimal myocardial edema and inflammation. Blood clots in the metastatic lesion of bone marrow aspirates exhibited positive staining for cardiac troponin-T and CK-MB in the cytoplasm and nucleoplasm of neoplastic cells. Although we did not perform a second cardiac magnetic resonance imaging and autopsy, we postulate that the attack of the neoplastic cells by the immune checkpoint inhibitor or the secretion from neoplastic cell-derived extracellular vesicles may have exacerbated the increase in concentrations of these molecules in the blood. Our case should warrant consideration a false-positive value of cardiac troponin-T and CK-MB can be obtained in cases with malignancy.